Patterns and Drivers of Health Spending Efficiency - Garcia-Escribano, Mercedes (IMF Working Papers; Working Paper ;, 2022)
Demands for ramping up health expenditures are at an all-time high. Countries' needs for additional health resources include responding to the COVID-19 pandemic, closing gaps in achieving the Sustainable Development Goal in health in most emerging and developing countries, and serving an ageing population in advanced economies. Facing limited fiscal space for raising health spending focuses policymakers' attention on ensuring that resources are used efficiently. How sizable are the potential gains-in terms of freeing up resources and delivering better health outcomes-from improving health spending efficiency? How has efficiency evolved over the past decade? What can policymakers do to boost it? This paper estimates health spending efficiency across countries using bias-corrected data envelopment analysis and finds sizable differences in efficiency across countries, in particular among emerging and developing countries compared to advanced economies. The examination of the evolution of efficiency reveals that important efficiency gains have been made in the majority of countries. The paper also explores some of the key drivers of efficiency and finds that lower income inequality, less corruption, and health interventions oriented at expanding population access to basic health services are associated with greater efficiency.